High vs. low radiotherapy dose in locally advanced esophageal squamous cell carcinoma patients treated with neoadjuvant concurrent chemoradiotherapy: an endemic area population-based study - Chia-Chin Li; Chih-Yi Chen; Ying-Hsiang Chou; Chih-Jen Huang; Hsiu-Ying Ku; Ying-Chun Lin; Chun-Ru Chien (Discover Oncology, 2022)
Abstract Background The optimal radiotherapy dose for locally advanced esophageal squamous cell carcinoma in endemic areas treated with neoadjuvant concurrent chemoradiotherapy is unclear. Methods Eligible patients diagnosed between 2010 and 2019 were identified via the Taiwan Cancer Registry. We used propensity score (PS) weighting to balance observable potential confounders. The hazard ratio (HR) of death was compared between high dose (50–50.4 Gy) and low dose (40–41.4 Gy) radiotherapy. We also evaluated other outcomes and performed supplementary analyses via an alternative approach. Results Our study population consisted of 644 patients. The PS weight-adjusted HR of death was 0.92 (95% confidence interval: 0.7–1.19, p = 0.51). There were no statistically significant differences for other outcomes or supplementary analyses. Conclusions In this population-based study from an endemic area, we found no significant difference in overall survival between high vs. low radiotherapy doses.